Preparing scientific application software for exascale computing - Åström, J. A.; Carter, A.; Hetherington, J.; Ioakimidis, K.; Lindahl, E.; Mozdzynski, G.; Nash, R. W.; Schlatter, Philipp; Signell, A.; Westerholm, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2013)
Many of the most widely used scientifc application software of today were developed largely during a time when the typical amount of compute cores was calculated in tens or hundreds. Within a not too distant future the number of cores will be calculated in at least hundreds of thousands or even millions. A European collaboration group CRESTA has recently been working on a set of renowned scientific software to investigate and develop these codes towards the realm of exascale computing. The codes are ELMFIRE, GROMACS, IFS, HemeLB, NEK5000, and OpenFOAM. This paper contains a summary of the strategies for their development towards exascale and results achieved during the first year of the collaboration project. © 2013 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Elmfire; Exascale; Gromacs; HemeLB; IFS; NEK5000; OpenFOAM; Optimization; Science Application Software